2012
DOI: 10.1063/1.4772797
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh conductivity of large area suspended few layer graphene films

Abstract: Photoconductivity and characterization of nitrogen incorporated hydrogenated amorphous carbon thin films J. Appl. Phys. 112, 113706 (2012) Diffusion thermopower in suspended graphene: Effect of strain J. Appl. Phys. 112, 093711 (2012) Charging of nanostructured and partially reduced graphene oxide sheets Appl. Phys. Lett. 101, 183109 (2012) Temperature dependence of reversible switch-memory in electron field emission from ultrananocrystalline diamond Appl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 28 publications
4
21
1
Order By: Relevance
“…Further, the conductivity decreased rapidly with increasing thickness when the number of graphene layers ranged from 2 to 13, but decreased slowly and thereafter remained constant for layer numbers up to 165. These numerical simulation results were in agreement of the published experimental results [133,134]. More information about the properties of monolayer, bilayer and few-layer graphene can be found in Refs [119,135139].…”
Section: The Structure Of Graphenesupporting
confidence: 89%
“…Further, the conductivity decreased rapidly with increasing thickness when the number of graphene layers ranged from 2 to 13, but decreased slowly and thereafter remained constant for layer numbers up to 165. These numerical simulation results were in agreement of the published experimental results [133,134]. More information about the properties of monolayer, bilayer and few-layer graphene can be found in Refs [119,135139].…”
Section: The Structure Of Graphenesupporting
confidence: 89%
“…From test results, shown in Figure 7(b), the slope of the I to V characteristics of graphene on the SiO 2 PC structure is 2.8 times as high as that on the planar substrate. The sheet resistance of graphene on the planar SiO 2 substrate is about 300 Ω/□ and the average sheet resistance of graphene on the PC structure is about 107 Ω/□, which is similar to other reports [15,22].…”
Section: Methodssupporting
confidence: 77%
“…Thus, the average velocity of the electrons [Eqs. (5) and (6)] can be substituted for the average velocity of thermal motion. For the 2D electron gas, the average velocity of the thermal motion of electrons is presented in Eq.…”
Section: Carrier Transport Channel and Their Scattering Mechanismmentioning
confidence: 99%
“…Boland et al [30] demonstrated that the electrical conductivity of GNRs decreases with increasing thickness; a similar behavior is observed for graphite. Rouhi et al [5] found that the electrical resistivity of suspended FLG is approximately 3.35 μ /cm. Hwang and Das Sarma [31] theoretically calculated the temperature-dependent electrical conductivity of graphene using the Boltzmann transport equation and the mechanism of phonon scattering.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation